2006
DOI: 10.1007/s10803-006-0242-7
|View full text |Cite
|
Sign up to set email alerts
|

Network Model of Decreased Context Utilization in Autism Spectrum Disorder

Abstract: Individuals with autism spectrum disorders (ASD) demonstrate impaired utilization of context, which allows for superior performance on the "false memory" task. We report the application of a simplified parallel distributed processing model of context utilization to the false memory task. For individuals without ASD, experiments support a model wherein presentation of one word, e.g., ''apple,'' strongly activates the neighboring nodes of closely related words such as ''fruit,'' ''tree,'' whereas in ASD these ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
(30 reference statements)
0
20
0
1
Order By: Relevance
“…A beneficial effect from propranolol can also be detected in Broca's aphasia patients struggling to perform a naming task (Beversdorf et al, 2007b). Whereas it is not certain whether norepinephrine is upregulated in autism (Lake et al, 1977;Launay et al, 1987;Barthelemy et al, 1988;Martineau et al, 1992;Minderaa et al, 1994;Martchek et al, 2006) or whether the restriction is more anatomical in nature (Belmonte et al, 2004), our preliminary findings begin to suggest that propranolol also has some benefit for performance of the hyper-restrictive networks proposed by network models of autism (Cohen, 1994;McClelland et al, 2000;Beversdorf et al, 2007a) (see Fig. 1).…”
Section: Noradrenergic System Cognition and Autismmentioning
confidence: 57%
“…A beneficial effect from propranolol can also be detected in Broca's aphasia patients struggling to perform a naming task (Beversdorf et al, 2007b). Whereas it is not certain whether norepinephrine is upregulated in autism (Lake et al, 1977;Launay et al, 1987;Barthelemy et al, 1988;Martineau et al, 1992;Minderaa et al, 1994;Martchek et al, 2006) or whether the restriction is more anatomical in nature (Belmonte et al, 2004), our preliminary findings begin to suggest that propranolol also has some benefit for performance of the hyper-restrictive networks proposed by network models of autism (Cohen, 1994;McClelland et al, 2000;Beversdorf et al, 2007a) (see Fig. 1).…”
Section: Noradrenergic System Cognition and Autismmentioning
confidence: 57%
“…Whereas it is not certain that norepinephrine is upregulated in autism (Martchek et al, 2006;Martineau et al, 1992;Minderaa et al, 1994) or whether the restriction is more anatomical in nature (Belmonte et al, 2004), our data suggests that the propranolol also has some benefit for performance of the hyper-restrictive networks proposed by network models of autism (Beversdorf, Narayanan, Hillier, & Hughes, 2007;Cohen, 1994;McClelland, 2000). In our study, the two groups did not appear to differ in how hemodynamic responses to propranolol related to cognitive responses to proproanolol.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, contrary to expectations, we found no differences in serial clustering between the ASD and comparison groups. Our prediction that individuals with ASD would demonstrate more serial clustering was based on the detail-focused cognitive style that has been previously described in individuals with ASD (Happé and Frith 2006), as well as the weak associative nodes suggested by the neural network hypothesis (Beversdorf et al 2007). It is possible that we did not find differences in these measures because our sample was high-functioning and we utilized a verbal task; Beversdorf et al (1998) suggested that impairments in recall thought to be associated with weak central coherence may be less evident in higher functioning individuals with ASD.…”
Section: Discussionmentioning
confidence: 73%
“…A higher serial cluster ratio among ASD participants relative to comparison participants was predicted based on the Weak Central Coherence (WCC) theory, which suggests that individuals with ASD have a more detail-oriented, bottom-up cognitive style (Happé and Frith 2006). This difference in strategy use among groups would also be predicted based on the network model of context use (Beversdorf et al 2007), which suggests that the high specificity (i.e., hypersensitivity) of memory encoding in individuals with ASD can be attributed to weaker associative neural node activation.…”
Section: Introductionmentioning
confidence: 95%